119P Final results of phase II trial (MIRACULUM) of the novel PD-1 inhibitor prolgolimab in patients with advanced melanoma. (15th December 2019) - Tjulandin, S; Fedyanin, M; Demidov, L; Moiseyenko, V; Protsenko, S; Odintsova, S; Semiglazova, T Y; Zukov, R; Lazarev, S; Andreev, A; Nechaeva, M; Makarova, J; et al.
Abstract: Background: MIRACULUM (NCT03269565) is a multicenter open-label parallel-arm phase II study investigating the antitumor activity of prolgolimab, an IgG1 anti-PD-1 monoclonal antibody with Fc silencing "LALA" mutation, in patients with advanced melanoma. Final analysis after ≥12 months of follow-up is presented. Methods: Patients (pts) with unresectable or metastatic melanoma, without autoimmune disease, no prior BRAF/MEK inhibitors, and anti-PD-1 or anti-CTLA-4 therapy were eligible. Pts received prolgolimab 1 mg/kg Q2W (arm 1) or 3 mg/kg Q3W (arm 2) until disease progression or intolerable toxicity. A statistical hypothesis that prolgolimab has significant anti-tumor effect (ORR more than 28%) was tested for each study arm. Results: 126 pts (63 in each arm) received at least one dose of prolgolimab (mITT population). Baseline pt characteristics were generally balanced between the arms. Prior systemic therapy was administered in 17 (27%) and 16 (25%) pts in arm 1 and 2, respectively. Stage II-III unresectable disease was observed in 4 (6.4%) pts in arm 1 and in 2 (3.2%) pts in arm 2. As of Feb 22, 2019, median follow-up was 13.8 mo (95%CI, 13.2-14.7) in arm 1 and 14.5 mo (95%CI, 13.9-15.2) in arm 2. The study met its primary endpoint in both study arms. In arm 1, 38% ORR was achieved, including 5 CR and 19 PR, and the disease control rate (DCR) was 64%. In arm 2, 29% ORR was achieved, including 2 CR and 16 PR, and the DCR was 46%. 12-mo OS rates were 74.6% for 1 mg/kg Q2W and 54.0% for 3 mg/kg Q3W. 12-mo PFS rates were 41.3% for 1 mg/kg Q2W and 34.9 for 3 mg/kg Q3W. Median response duration was not reached; 83% of all responses were ongoing at data cutoff. Treatment-related AEs (TRAEs) occurred in 55.6% and 54.0% of pts, including 12.7% and 3.2% with grade 3-4 TRAEs in arm 1 and 2, respectively. Immune-related AEs (irAEs) occurred in 36.5% of pts in arm 1 and 34.9% of pts in arm 2, including 7.4% and 1.6% of pts with grade 3/4 irAEs in each arm. Conclusion: Both dosing regimens of prolgolimab (1 mg/kg Q2W and 3 mg/kg Q3W) have durable antitumor activity and a manageable safety profile in patients with advanced melanoma. Clinical trial identification: NCT03269565. Legal entity responsible for the study: BIOCAD. Funding: BIOCAD. Disclosure: S. Tjulandin: Advisory / Consultancy, Speaker Bureau / Expert testimony: BIOCAD. M. Fedyanin: Advisory / Consultancy, Speaker Bureau / Expert testimony: BIOCAD. L. Demidov: Advisory / Consultancy, Speaker Bureau / Expert testimony: BIOCAD. V. Moiseyenko: Research grant / Funding (institution): BIOCAD. S. Protsenko: Advisory / Consultancy, Speaker Bureau / Expert testimony: BIOCAD. S. Odintsova: Speaker Bureau / Expert testimony: BIOCAD. T.Y. Semiglazova: Advisory / Consultancy, Speaker Bureau / Expert testimony: BIOCAD. M. Nechaeva: Speaker Bureau / Expert testimony: BIOCAD. O. Kozlova: Full / Part-time employment: BIOCAD. M. Shustova: Full / Part-time employment: BIOCAD. A. Garipov: Full / Part-time employment: BIOCAD. R. Ivanov: Full / Part-time employment: BIOCAD. All other authors have declared no conflicts of interest.